2004
DOI: 10.1002/ppul.20019
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco smoke exposure, wheeze, and atopy

Abstract: We investigated the effect of in utero and postnatal environmental tobacco smoke (ETS) exposure on respiratory symptoms and atopy in the first 3 years of life in children at high risk of allergic disease (both parents atopic). Three hundred and sixty-nine children were followed from birth and reviewed at ages 1 and 3 years (respiratory questionnaire, skin testing). Parental smoking questionnaires were administered, and plasma cotinine in cord and peripheral blood (at age 1 year) was measured (capillary column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 26 publications
3
53
0
4
Order By: Relevance
“…Thirty-one of the 71 studies (44%) were scored as being of moderate or high level (.6) methodological quality. The main reasons for lower NOS scores were lack of an objective measure of smoking since the vast majority relied upon self-reported smoking (only 1 study provided objective data in the form of cotinine levels 17 ), lack of adjustment for confounding factors, and lack of study sample representativeness due to restrictions to children whose parents had an allergic disease.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-one of the 71 studies (44%) were scored as being of moderate or high level (.6) methodological quality. The main reasons for lower NOS scores were lack of an objective measure of smoking since the vast majority relied upon self-reported smoking (only 1 study provided objective data in the form of cotinine levels 17 ), lack of adjustment for confounding factors, and lack of study sample representativeness due to restrictions to children whose parents had an allergic disease.…”
Section: Resultsmentioning
confidence: 99%
“…19 There was also 1 study that used an objective measure of passive smoke exposure and revealed that children with detectable cord blood levels were not at significantly increased risk of wheeze at age 1 or 3 years or of wheeze at age 3 years in relation to blood cotinine levels at age 1. 17 …”
Section: Figurementioning
confidence: 99%
“…Studies have used cotinine levels obtained from meconium, umbilical cord blood, and maternal hair, urine, or serum to assess prenatal tobacco exposure and have associated increased levels with increased respiratory symptoms and asthma in children. 14,[18][19][20][21] One study performed in adults explored the relationship between cotinine levels and asthma-related hospital admissions; however, this study found that higher hair concentrations of nicotine, but not cotinine, were associated with increased rates of hospitalization. 22 Another study linked urine cotinine levels to hospitalizations for bronchiolitis in infants.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies investigating the incidence of respiratory symptoms during childhood were either conducted in older children, 20,21 selected high risk populations, 8,9,22 were retrospective, 23 or focused on wheeze only. 7,11,12 Only few studies assessed prospectively incidence of both cough and wheeze in unselected infants (Table 4).…”
Section: Frequency Of Respiratory Symptomsmentioning
confidence: 99%
“…Most authors have studied high-risk children, hospitalized for acute or chronic illness or with a family history of atopy. 8,9 Because of the high costs involved in prospective studies, symptoms have usually been assessed retrospectively, a method hampered by recall bias. In addition, most studies have been limited to wheeze, while incidence of cough has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%